A Case Report to Assess Passive Immunity in a COVID Positive Pregnant Patient - Toner, Lorraine E.; Gelber, Shari E.; Pena, Juan A.; Fox, Nathan S.; Rebarber, Andrei (American Journal of Perinatology, 2020)
Introduction Data regarding transplacental passage of maternal coronavirus disease 2019 (COVID-19) antibodies and potential immunity in the newborn is limited.Case Report We present a 25-year-old multigravida with known red blood cell isoimmunization, who was found to be COVID-19 positive at 27 weeks of gestation while undergoing serial periumbilical blood sampling and intrauterine transfusions. Maternal COVID-19 antibody was detected 2 weeks after positive molecular testing. Antibodies were never detected on cord blood samples from two intrauterine fetal cord blood samples as well as neonatal cord blood at the time of delivery.Conclusion This case demonstrates a lack of passive immunity of COVID-19 antibodies from a positive pregnant woman to her fetus, neither in utero nor at the time of birth. Further studies are needed to understand if passage of antibodies can occur and if that can confer passive immunity in the newborn.Key Points
Keywords: SARS-CoV-2; pregnancy; COVID-19; passive immunity